“CHANGING MEANINGS: THE ROLE OF SOCIETY IN INFLUENCING SEMANTIC SHIFTS IN ENGLISH” - Eshonqulov Ravshan Toxirovich; Jurayev Azizbek Ikromjon ugli (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
This article examines the phenomenon of semantic change in the English language, focusing on the role of social influences in driving shifts in word meanings. By analyzing how movements, digital culture, and technological advancements shape language, the study highlights how English evolves in response to societal shifts. Drawing on works by influential linguists and authors such as Raymond Williams, George Orwell, and David Crystal, the article discusses key examples of words that have taken on new connotations in alignment with modern social values. Through these examples, the article illustrates how social forces not only introduce new vocabulary but also repurpose existing words to meet the expressive needs of each generation. Ultimately, this exploration underscores the adaptability of language as a reflection of cultural change, showing how English remains resilient and relevant in an ever-evolving world.